ABA DOA (Android-Based Attendance for D-III Accounting Lecturers) Using the USU Vocational Faculty Location Authorization Feature - Machfudz, Emir Syarif; Sinaga, Annisa Fitri; Zufria, Ilka; Syarif, Firman (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Abstract This research details the development of Android-based Attendance Application for D-III Accounting Lecturers (ABA DOA) using Appsheet platform and utilizing LATLONG() and DISTANCE() functions for location validation. The development method applied is Rapid Application Development (RAD). ABA DOA provides convenience for lecturers with a self-photo feature as proof of validation, while integrating GPS and Google Maps to validate the location of attendance. The application results show efficiency in academic management with an optimal level of security. The LATLONG() function is used to determine the location coordinate point, while DISTANCE() is used to measure the distance between the authorized coordinate point and the attendance location. This research highlights the importance of technological innovation in supporting academic activities and campus management. The conclusion of this research is that ABA DOA successfully optimizes the attendance process with a high level of validation and security, making a positive contribution to the efficiency and effectiveness of study program management.